Implementasi Pembelajaran Pendidikan Agama Islam dan Budi Pekerti Berbasis Multiliterasi - Maulidiyah, Husnul; Sukarno, Sukarno; Muhith, Abd (Pendidikan Islam Pascasarjana IAIN Jember, 2024)
ABSTRACT The effectiveness of Islamic Religious Education learning in schools requires attention from all educators, especially the problem of multiliteracy. Many students who lack literacy when graduating from educational institutions that implement a multiliteracy program with the aim of instilling character or habits of multiliteracy for students. The focus of this study is 1. How is the planning of Islamic Religious Education and Character Education based on Multiliteracy at SMPN Sukorambi?; 2. How is the implementation of Islamic Religious Education and Character Education based on Multiliteracy at SMPN Sukorambi?; 3. How is the evaluation of Islamic Religious Education and Character Education based on Multiliteracy at SMPN Sukorambi? The effectiveness of Islamic Religious Education (PAI) learning requires attention, especially related to the problem of multiliteracy, because many students are less literate after graduating. SMP Negeri 1 Sukorambi implements a multiliteracy program to instill character and literacy habits in students. This study focuses on: 1) planning of Islamic Religious Education learning based on multiliteracy, 2) implementation of learning, and 3) evaluation of learning at the junior high school. The study aims to analyze the three aspects using a descriptive qualitative approach with data collection techniques in the form of observation, interviews, and documentation. Data were analyzed through condensation, presentation, and verification, with data validity checked through triangulation. The results of the study of Islamic Religious Education and Character Education Learning planning based on multiliteracies involve planning RPPs that are prepared together with teachers and curriculum vice principals according to office regulations, with literacy integration in the material. Its implementation follows the 2013 curriculum with a time allocation of 3 x 40 minutes per week, 25 students per class, and includes preliminary, core, and closing activities, carried out in class or the library with students' obligations to produce written work. Evaluation includes assessment of knowledge (assignments, tests, PTS, PAS), attitudes (observation, peer assessment, behavior), and skills (oral tests, practice, memorization, and written work). schools make a generation of young people who are minimal in literacy. So it is necessary to instill various methods to overcome the problem of multiliteracy. At SMP Negeri 1 Sukorambi